Learning to learn in preschool: Principles for a framework concerning preschool teacher empowerment - Cristina Stringher (Pensa MultiMedia, 2023)
The European preschool sector is receiving increased attention. The European Council Recommendations (2018; 2019) emphasize the need for ECEC to be at the forefront in developing teaching practices conducive to key competences. Among these, Learning to Learn (L2L), crucial at this developmental stage. Italian preschool is of good quality and inclusive. However, the 2019-2020 self-evaluation round evidenced some weaker areas. Only 28.7% of leaders declare that children in their preschool have a positive self-esteem. In addition, teachers seem unaware of L2L in early childhood and hold misconceptions on its acquisition. This contribution advances an evidence-based trajectory for preschool teachers' in-service training on L2L, framed within a sociocultural perspective, for their empowerment. The core of this proposal is to uncover teachers' L2L conceptions that are generally unconscious. Reflecting on their own L2L, teachers are empowered and able to prepare a preschool environment where children may acquire self- and co-regulated learning competences.